1999
DOI: 10.1021/jp993390o
|View full text |Cite
|
Sign up to set email alerts
|

β-Fragmentation and Other Reactions Involving Aminyl Radicals from Amino Acids

Abstract: Aminyl radicals, HN•−CR2−CO2 - (R = H, CH3) have been identified as significant transients in the hydroxyl radical-induced oxidation of the anions of glycine (Gly-), alanine (Ala-), and α-methylalanine (MeAla-) at relative yields of 37%, 43%, and 56%, respectively. Quantification has been achieved by two independent pulse radiolysis methods. Direct titration of the aminyl radicals made use of their capability to oxidize hydroquinone to the easily detectable semiquinone radical. The rate constant for this react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
91
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(103 citation statements)
references
References 22 publications
11
91
0
Order By: Relevance
“…Aminyl radicals have also been detected indirectly during the reaction of hydroxyl radicals (HO ) or their conjugated base ( O À ) with the free amino group of amino acids (Reactions (3.9) and (3.10)) [40][41][42][43], and identified by time-resolved EPR experiments [44]. Similar reactions may be expected for peptides.…”
Section: Generation Of Aminyl and Amidyl Radicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aminyl radicals have also been detected indirectly during the reaction of hydroxyl radicals (HO ) or their conjugated base ( O À ) with the free amino group of amino acids (Reactions (3.9) and (3.10)) [40][41][42][43], and identified by time-resolved EPR experiments [44]. Similar reactions may be expected for peptides.…”
Section: Generation Of Aminyl and Amidyl Radicalsmentioning
confidence: 99%
“…In their studies on the radical-induced decarboxylation of Gly anion, Bonifačić et al observed a protoncatalyzed decarboxylation of H 2 NaC HaCO 2 À , which may proceed via Reactions (3.16)-(3.18)[40,41]. In their studies on the radical-induced decarboxylation of Gly anion, Bonifačić et al observed a protoncatalyzed decarboxylation of H 2 NaC HaCO 2 À , which may proceed via Reactions (3.16)-(3.18)[40,41].…”
mentioning
confidence: 99%
“…Our studies on radiolytic and photolytic oxidation reactions of aminocarboxylate ions have provided a significant advance in understanding the mechanism of OH attack. [5][6][7][8] Complementary electronic structure calculations have yielded insight into the mechanism of the radiolytic oxidation in the model complexants glycine and its methylated derivatives. 5,6 Attack by the hydroxyl radical in basic solution had previously been shown to produce a carbon-centered radical, presumably via hydrogen abstraction.…”
Section: Reactions Of No 2 Radicals and The Effect Of No 2 -mentioning
confidence: 99%
“…[5][6][7][8] Complementary electronic structure calculations have yielded insight into the mechanism of the radiolytic oxidation in the model complexants glycine and its methylated derivatives. 5,6 Attack by the hydroxyl radical in basic solution had previously been shown to produce a carbon-centered radical, presumably via hydrogen abstraction. 9 Theoretical predictions of prompt decarboxylation following electron transfer to give the aminomethyl radical, 6 and suggestions that competitive H-abstraction would produce the aminyl radicals previously inferred from pulse radiolysis studies, 5 have been verified by observations of both radical products by time-resolved EPR spectroscopy (TRESR) and spin trapping experiments.…”
Section: Reactions Of No 2 Radicals and The Effect Of No 2 -mentioning
confidence: 99%
See 1 more Smart Citation